Solar Energy Harvesting for Wireless Sensor Network - Hong, Timothy Ngi Ing (Universiti Teknologi PETRONAS, 2014)
Typically wireless sensor motes are operated by using small batteries because batteries are small in size and able to provide the sufficient energy for the motes. However batteries could not sustain the energy for the motes to operate for a long period. This is because the degradation of batteries could reduce the useable lifetime of the motes system. Besides that, batteries have limited energy capacity which could used up eventually. Aside from relying on the batteries to power up motes, one of the way to sustain the system is to harvest the sources of energy from the environment such as light, vibration, and thermal. These energies are renewable energy which does not cause pollution to the environment. In this project, solar energy harvesting have been proposed to sustain the energy requirement for the motes to operate. Experiments have been conducted to observe the solar panel charging characteristic to improve the efficiency and effectiveness of charging circuit to minimize the power loss. There are three main element in solar energy harvesting which are photovoltaic (PV) modules, solar charge controller and also energy storage. Based on the calculation, suitable PV modules, charging circuit and batteries are determined. Maximum Power Point Tracking (MPPT) technique are used for the charging circuit to maximize the efficiency conversion of the energy harvested from solar panel to charge the rechargeable lithium ion battery.